The FinO/ProQ-like protein PA2582 impacts antimicrobial resistance in Pseudomonas aeruginosa - Cianciulli Sesso, Anastasia; Resch, Armin; Moll, Isabella; Bläsi, Udo; Sonnleitner, Elisabeth (Frontiers in Microbiology, 2024)
Bacteria employ small regulatory RNAs (sRNA) and/or RNA binding proteins (RBPs) to respond to environmental cues. In Enterobacteriaceae, the FinO-domain containing RBP ProQ associates with numerous sRNAs and mRNAs, impacts sRNA-mediated riboregulation or mRNA stability by binding to 5'-or 3'-untranslated regions as well as to internal stem loop structures.Global RNA-protein interaction studies and sequence comparisons identified a ProQ-like homologue (PA2582/ProQ Pae ) in Pseudomonas aeruginosa (Pae). To address the function of ProQ Pae , at first a comparative transcriptome analysis of the Pae strains PAO1 and PAO1ΔproQ was performed. This study revealed more than 100 differentially abundant transcripts, affecting a variety of cellular functions. Among these transcripts were pprA and pprB, encoding the PprA/PprB two component system, psrA, encoding a transcriptional activator of pprB, and oprI, encoding the outer membrane protein OprI. RNA co-purification experiments with Strep-tagged Pae ProQ protein corroborated an association of ProQ Pae with these transcripts. In accordance with the up-regulation of the psrA, pprA and pprB genes in strain PAO1ΔproQ a phenotypic analysis revealed an increased susceptibility towards the aminoglycosides tobramycin and gentamicin in biofilms. Conversely, the observed down-regulation of the oprI gene in PAO1ΔproQ could be reconciled with a decreased susceptibility towards the synthetic cationic antimicrobial peptide GW-Q6. Taken together, these studies revealed that ProQ Pae is a RBP that impacts antimicrobial resistance in Pae.